It's a whole spiel : love, latkes, and other Jewish stories - Locke, Katherine; Silverman, Laura (Alfred A. Knopf, 2019)
"From stories of confronting their relationships with Judaism to rom-coms with a side of bagels and lox, It's a Whole Spiel features one story after another that says yes, we are Jewish, but we are also queer, and disabled, and creative, and political, and adventurous, and anything we want to be"--